2019
DOI: 10.1021/acs.jpcb.9b01571
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Short Hydrogen Bonds in Photoactive Yellow Protein via Noncanonical Amino Acid Incorporation

Abstract: Photoactive yellow protein (PYP) is a small photoreceptor protein that has two unusually short hydrogen bonds between the deprotonated p-coumaric acid chromophore and two amino acids, a tyrosine and a glutamic acid. This has led to considerable debate as to whether the glutamic acid-chromophore hydrogen bond is a low barrier hydrogen bond, with conflicting results in the literature. We have modified the pK a of the tyrosine by amber suppression and of the chromophore by chemical substitution. X-ray crystal str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…The absorption spectra of the PYP constructs are shown in Figure 4A with peak values listed in Table 3. Bromination of the pCA chromophore within PYP causes a small blue shift of 1 nm, similar to the observed blue shift for other halogenated chromophores in PYP [25] and other fluorescent proteins [30,31]. Franck-Condon excitation is purely an electronic process that reflects the electronic properties of the chromophore and the effect of the environment at the instantaneous moment of photon absorption before any atomic rearrangements.…”
Section: Uv-vis Absorption and Fluorescence Spectroscopysupporting
confidence: 72%
See 2 more Smart Citations
“…The absorption spectra of the PYP constructs are shown in Figure 4A with peak values listed in Table 3. Bromination of the pCA chromophore within PYP causes a small blue shift of 1 nm, similar to the observed blue shift for other halogenated chromophores in PYP [25] and other fluorescent proteins [30,31]. Franck-Condon excitation is purely an electronic process that reflects the electronic properties of the chromophore and the effect of the environment at the instantaneous moment of photon absorption before any atomic rearrangements.…”
Section: Uv-vis Absorption and Fluorescence Spectroscopysupporting
confidence: 72%
“…Synthesis of the 3-bromo-pCA (3-Br-pCA) chromophore derivative followed by functionalization to the corresponding acid anhydride and linkage to the thiol of C69 yielded a PYP construct with the modified chromophore (PYP 3-Br-pCA, see Materials and Methods). Similar approaches in our lab and others have produced PYP variants with a less electron-rich substituent on the phenolate ring of pCA such as a hydroxy group [21][22][23], methoxy group [21,24], and chlorine atom [25]. Note that substituents have also been placed at the α position of the carboxylic acid of pCA (C3 in Fig.…”
Section: Incorporation Of Heavy Atomsmentioning
confidence: 86%
See 1 more Smart Citation
“…17 The proposal 6 that the HC4 E46 HB is a LBHB has led to many new experimental and theoretical studies. [18][19][20][21][22][23][24][25] Nearly, all of these studies (with single exception 22 ) have consistently showed that the HC4 E46 HB is not a LBHB. One study attempted to reconcile disagreements with new theoretical approaches, 22 but the validity of the new approaches has been questioned.…”
Section: Introductionmentioning
confidence: 98%
“…The proposal that the HC4E46 HB is a LBHB has led to many new experimental and theoretical studies . Nearly, all of these studies (with single exception) have consistently showed that the HC4E46 HB is not a LBHB.…”
Section: Introductionmentioning
confidence: 99%